A Rare case of pneumoperitoneum in pregnancy: Perforation of Tubercular ileal Ulcer - Richmond Ronald Gomes (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2021)
The incidence of Tuberculosis (TB) is rising worldwide, despite the efficacy of the BCG vaccination. Populations at greatest risk of contracting TB are migrant communities, as well as immunocompromised individuals. The diagnosis of intestinal tuberculosis can often present as a diagnostic conundrum, due to its nonspecific and varied presentation, often mimicking inflammatory bowel disease or malignancy. Free perforation is one of the most feared complications of the intestinal tuberculosis. The terminal ileum is the most common site of perforation, while the majority of (90%) perforations are solitary. We present a 25 year old 17 weeks primi presented with peritonitis with solitary perforation of terminal ileum with miscarriage of fetus and subsequent surgical wedge resection of ileum and ileo-ileal anastomosis. Histology revealed presence of Langerhan's cell with caseating granulomatous inflammation. There was no radiological evidence of pulmonary tuberculosis. Patient was started on anti-tubercular therapy and responded well. This present case underscores the importance of biopsy specimens taken from the margins of patients with ileal perforation to avoid the misdiagnosis of such condition.